(3GdcjGSI aj CMcGe GdSjGSIs ((3UGdMjI OeTb s)
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai GdGLJgGO dg Cf jNQL faSI ef GdXdeI hCf Hchf ef GdGFeI GdYGOdjf s
(3BNQgG (B:s
(3jfJgi HGdHGH GdYTQhf ai GdGMcGe heG jJYdb HgG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs